Dynamic modelling and characterisation of a two-link flexible robot manipulator - Khairudin, Mohammad (Sage Journals, 2010)
This paper presents an investigation into the dynamic modelling and characterisation of a two-link flexible robot manipulator. A planar two-link flexible manipulator incorporating structural damping, hub inertia and payload that moves in the horizontal plane is considered. A dynamic model of the system is developed using a combined Euler-Lagrange and assumed mode method. Simulation is performed to assess the dynamic model and system responses at the hub and end-point of both links are presented and analysed in time and frequency domains. Moreover, effects of payload on the dynamic characteristics of the flexible manipulator are studied and discussed.